Women writing history : three generations - Romila Thapar; Kumkum Roy; Preeti Gulati (New Delhi : Zubaan, 2025)
"Three historians. Three generations. Spanning nearly a century of work, Romila Thapar, Kumkum Roy and Preeti Gulati, reflect on their lives and their engagement with one of the most demanding, and most crucial, disciplines of our times. Personal narratives of growing up$1 (Blearning about history, charting new and distinct paths as researchers, the challenges of teaching$1 (Bmeld effortlessly into a larger and complex changing context: the emergence of an independent nation, of movements that have helped shape the process, and of resistance. To what extent, the authors ask, have feminisms made a difference? Can these interventions lead to redefining or rejuvenating the discipline, transforming it into a more inclusive space where diverse voices can be acknowledged and heard with respect and understanding? These and other questions inform this accessible and lucid text."s
Keywords: Historiography; History